Strategic management accounting : a practical guidebook with case studies - Li, Wing Sun (Management for professionals., 2018)
This book serves as a guide to strategic management accounting. It introduces new and useful concepts on how to collect, analyse, and evaluate options to enable managers to steer corporate directions and write strategic plans for the long-term success of the corporation. Starting with basic techniques and the latest strategic management approaches, the book then presents cases that show the techniques employed step by step. By demonstrating how easily the ideas can be translated into action, it is a valuable resource for business practitioners, as well as for students taking advanced management accounting courses.